Rozwój gospodarki budżetowej państwa i rad narodowych w trzydziestoleciu Polski Ludowej - Denek, Emilia; Wierzbicki, Janusz (Wydział Prawa i Administracji UAM, 1975)
The authors examine the evolution of budgets lin Poland from 1944 in four following periods: 1) period of the dualism of State and local authorities till 1950; 2) period of the creation of the uniform State authorities after 1951; 3) period of the improving of the budgetary system till 1970; 4) period of the discussion and preparation prior to the new reform of the budgetary system. The peculiarity of both the State and local budgets in the first period was the following of the pre-war budget organization connected with the attempts to elaborate the new form of the budget revenue from State enterprises as well as the new form of budget financing of investment. In 1951 State and local budgets were integrated into the so-called collective State budget which at the same time became subordinated to the national economic plan. This integration was accompanied by important changes in the structure and implementation of the budget. In the third period after 1956, many more or less important improvements of the budget economy were introduced aiming at safeguarding the local initiative and activity based on the financial independence of the local authorities in the framework of collective budget. At the same time the budget was supplemented by quasi-budget funds of various kinds. Many significant changes were also introduced limiting the budget financing of State enterprises and their investment. From 1971, the new reform of budgetary system has been opened to discussion. In this article the authors present the main trends and themes of this discussion.
Evolution of the State and Local Budgets in the Polish People's Republic, 1944 - 1974